The Impact of Conventional Cigarettes, Nicotine-containing, and Nicotine-free Electronic Cigarettes on Testicular Weight of Male Wistar Rats - Silitonga, Hanna Tabita Hasianna; Rambung, Etha; Sekarputri, Cempaka Harsa; Nugraheni, Elizabeth Sulastri; Mellyanawati, Mellyanawati (Poltanesa, 2024)
E-cigarettes are gaining increasing popularity worldwide. The World Health Organization (WHO) estimates that there are nearly one billion (984 million) smokers globally, accounting for approximately one-fifth of the adult population. The use of e-cigarettes in Southeast Asian countries has also seen a rise since 2015, although at a slower pace compared to high-income countries. Presently, Indonesia has the highest prevalence of e-cigarette use in Southeast Asia at 11.8%, while Thailand has the lowest prevalence at 3.3%. Testes play a crucial role in male reproductive function. Decreased testicular size can lead to disruptions in testicular function, resulting in infertility. Testicular size is significantly correlated with sperm density in both fertile and infertile men. The objective of this study is to investigate changes in testicular weight due to exposure to conventional cigarettes, nicotine-containing, and nicotine-free e-cigarettes. This experimental research utilizes a post-test control only design. The sample comprises 24 male Wistar rats divided into four groups: Group A (control), Group B (exposed to conventional cigarettes), Group C (exposed to nicotine e-cigarettes), and Group D (exposed to non-nicotine e-cigarettes). Exposure to cigarettes lasts for 30 days, after which the rats undergo surgery to remove their testes. The research findings indicate a decrease in testicular size due to exposure to conventional cigarettes, nicotine e-cigarettes, and non-nicotine e-cigarettes. There is no significant difference observed among the three types of exposure. In conclusion, conventional cigarettes, nicotine-containing, and nicotine-free e-cigarettes elicit similar effects in reducing testicular weight in male Wistar rats.